'Mixed Blood' and Aesthetic Evolution in China's Electroacoustic Music Today. Issue 3 (12th December 2022) - De Ritis, Anthony Paul
Abstract : Current trends in the works of Chinese composers and their electroacoustic music today embrace increased abstraction and individual self-expression, while others celebrate the importance of clear communication and a unified 'Chinese model'. How is one to derive the current state of a Western art form imported by China, in the context of unparalleled sharing and convergence of ideas made possible by the internet and extensive intercultural exchange in today's globalised world? And how important is it to identify and measure the level of Chineseness in the artistic output of today's electroacoustic music composers that embrace Chinese elements – whether born inside or outside of China? This article seeks to unpack some of the current thinking shared by institutional leaders, such as Yu Feng, president of the Central Conservatory of Music; scholars of Chinese electroacoustic music, such as Marc Battier, Ken Fields, Leigh Landy, Yang Yinuo and Annie Yen-Ling Liu; and several composers and thought leaders in the most recent generations of Chinese electroacoustic music.